Transaction costs: A high financial burden for German home buyers - Michael Voigtländer (Institut der deutschen Wirtschaft (IW), 2016)
Home buyers in Germany not only have to pay high down payments for financing their property, but they also have to pay high transaction costs. Besides the transaction tax, also notary fees and the entry in the land register sum up to a considerable amount. The cases of the Netherlands and the United Kingdom illustrate that high transaction costs are not a necessity.
Keywords: 330